Design of a metadata framework for environmental models with an example hydrologic application in HydroShare. (July 2017) - Morsy, Mohamed M.; Goodall, Jonathan L.; Castronova, Anthony M.; Dash, Pabitra; Merwade, Venkatesh; Sadler, Jeffrey M.; Rajib, Mohammad Adnan; Horsburgh, Jeffery S.; Tarboton, David G.
Abstract: Environmental modelers rely on a variety of computational models to make predictions, test hypotheses, and address specific problems related to environmental science and natural resource management. Scientists and engineers must devote significant effort to preparing these computational models. While significant attention has been devoted to sharing and reusing environmental data, less attention has been devoted to sharing and reusing environmental models. A first step toward increasing environmental model sharing and reuse is to define a general metadata framework for models that is flexible and, therefore, applicable across the wide variety of models used by environmental modelers. This paper proposes a general approach for representing environmental model metadata that extends the Dublin Core metadata framework. The framework is implemented within the HydroShare system and applied for a hydrologic model sharing use case. This example application demonstrates how the metadata framework implemented within HydroShare can assist in model sharing, publication, reuse, and reproducibility. Highlights: The design of a metadata framework for model programs and instances is presented. The metadata framework is implemented within the HydroShare system. The framework is built from general standards like RDF, Dublin Core, and BagIt. The implementation is demonstrated for a hydrologic model publication use case. The implementation assists in model sharing, publication, reuse and reproducibility.